The Possibilities and Challenges of ICT in Education - Vats, Kunal; Singh, Barun Kr (Journal of Innovation in Education and Social Research, 2023)
The integration of Information and Communication Technology (ICT) in education offers significant potential to transform teaching and learning processes. This research paper explores the possibilities and challenges associated with ICT in education, highlighting its benefits, implementation hurdles, and the role it plays in modern educational paradigms. Various data tables provide quantitative insights into ICT adoption rates, benefits, and challenges, and references from the current literature are included to substantiate the discussion.